Evaluation of a SUMO E2 Conjugating Enzyme Involved in Resistance to Clavibacter michiganensis Subsp. michiganensis in Solanum peruvianum, Through a Tomato Mottle Virus VIGS Assay - Esparza-Araiza, Mayra J.; Bañuelos-Hernández, Bernardo; Argüello-Astorga, Gerardo R.; Lara-Ávila, José P.; Goodwin, Paul H.; Isordia-Jasso, María I.; Castillo-Collazo, Rosalba; Rougon-Cardoso, Alejandra; Alpuche-Solís, Ángel G. (Frontiers in Plant Science, 2015)
Clavibacter michiganensis subsp. michiganensis (Cmm) causes bacterial wilt and canker of tomato. Currently, no Solanum lycopersicum resistant varieties are commercially available, but some degree of Cmm resistance has been identified in Solanum peruvianum. Previous research showed up-regulation of a SUMO E2 conjugating enzyme (SCEI) transcript in resistant S. peruvianum compared to susceptible S. lycopersicum following infection by Cmm. In order to test the role of SCEI in resistance to Cmm, a fragment of the gene from S. peruvianum was cloned into a novel virus-induced gene-silencing (VIGS) vector based on the geminivirus Tomato Mottle Virus (ToMoV). Using biolistic inoculation, the ToMoV-based VIGS vector was shown to be effective in S. peruvianum by silencing the magnesium chelatase gene, which resulted in leaf bleaching. The ToMoV_SCEI construct resulted in approx. 61% silencing of SCEI in leaves of S. peruvianum as determined by quantitative RT-PCR. VIGS of SCEI in S. peruvianum resulted in unilateral wilting (15 dpi) and subsequent death (20 dpi) of the entire plant after Cmm inoculation, whereas empty vector-treated plants only showed wilting in the Cmm-inoculated leaf. SCEI-silenced plants also showed higher Cmm colonization with an average of 4.5 times more damaged tissue compared to the empty vector control plants. SCEI appears to play an important role in the innate immunity of S. peruvianum against Cmm, perhaps through the regulation of WRKY transcription factors, which may lead to expression of proteins involved in salicylic acid-dependent defense responses.